Classical trajectory study of adsorption and surface diffusion of Si on Si(100) - Ibrahim Ali , Noorbatcha; Lionel M. , Raff; Donald L. , Thompson (American Institute of Physics (AIP), 1984)
Adsorption and surfacediffusion of silicon on the Si(100) plane have been investigated by classical trajectory methods using a realistic potential‐energy surface. The calculated sticking probability for adsorption is 0.965 at 1500 K and is independent of temperature. The diffusion coefficient for Si on Si(100) is evaluated by modeling the diffusion process as the jumping of the adatom from one adsorption site to another. The diffusion coefficient calculated by this approach is given by D=(6.35±1.44)×10− 4 exp(−3.63±0.47 kcal mol− 1/R T) cm2 s− 1. This value is found to be in good agreement with the diffusion coefficients calculated from the long‐time behavior of the mean square displacement and from the integrated velocity autocorrelation function. The activation energy for diffusion is found to be less than the reported experimental value of 4.6 kcal mol− 1 for the diffusion of Si on Si(111). The diffusion of Si on Si(100) is found to be directional, occurring only along channels described by the intersection of the (022̄) planes with the (110) plane. Transverse diffusion in directions described by the intersection of the (022) planes with the (100) plane is a much higher‐energy process.